Long-term functional outcome following minimally invasive endoscopic intracerebral hemorrhage evacuation. (8th January 2020) - Kellner, Christopher P; Song, Rui; Pan, Jonathan; Nistal, Dominic A; Scaggiante, Jacopo; Chartrain, Alexander G; Rumsey, Jamie; Hom, Danny; Dangayach, Neha; Swarup, Rupendra; Tuhrim, Stanley; Ghatan, Saadi; et al.
Abstract : Background and purpose: Preclinical studies suggest that clot removal may mitigate primary and secondary brain injury following intracerebral hemorrhage (ICH). Although the MISTIE trial did not demonstrate an overall outcome benefit, it did demonstrate outcome benefit from effective reduction of clot burden. Minimally invasive endoscopic ICH evacuation may provide an alternative option for clot evacuation. Methods: Patients presenting to a single healthcare system from December 2015 to October 2018 with supratentorial spontaneous ICH were evaluated for minimally invasive endoscopic evacuation. Inclusion and exclusion criteria were prospectively established by a multidisciplinary group in the healthcare system. The prespecified primary analysis was the proportion of patients with modified Rankin Score (mRS) 0–3 at 6 months. Results: One hundred patients met the inclusion and exclusion criteria and underwent minimally invasive endoscopic ICH evacuation. The mean (SD) hematoma size was 49.7 (30.6) mL, the mean (SD) evacuation percentage was 88.2 (20.3)%, and 86% of patients had postoperative residual hematoma ≤15 mL. At 6 months the proportion of patients with an mRS of 0–3 was 46%. Conclusions: This study suggests that minimally invasive endoscopic ICH evacuation may produce favorable long-term functional outcomes. Further evaluation of this technique in a randomized clinical trial is necessary.